2007
DOI: 10.1213/01.ane.0000268713.58174.cc
|View full text |Cite
|
Sign up to set email alerts
|

Hemoximetry as the “Gold Standard”? Error Assessment Based on Differences Among Identical Blood Gas Analyzer Devices of Five Manufacturers

Abstract: The variance of sO2 measurements between identical devices increased significantly when saturation decreased from the normal level of 97% to the hypoxemic levels of 85% and 75%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…When SpHb values were compared to a reference laboratory device in our study, we found a higher standard deviation than what has been reported for Hb measurements from consecutive blood samples run on the same model lab device [33]. However, the standard deviation of SpHb to Hb in our study was similar to that found for Hb measurements from consecutive blood samples analyzed on two separate laboratory devices [34].…”
Section: Discussionsupporting
confidence: 74%
“…When SpHb values were compared to a reference laboratory device in our study, we found a higher standard deviation than what has been reported for Hb measurements from consecutive blood samples run on the same model lab device [33]. However, the standard deviation of SpHb to Hb in our study was similar to that found for Hb measurements from consecutive blood samples analyzed on two separate laboratory devices [34].…”
Section: Discussionsupporting
confidence: 74%
“…Several physiologic variables such as body position, blood source (e.g., arterial vs. peripheral venous), and time may influence the accuracy of tHb. [13][14][15] To eliminate some of these variables, we used the same sampling site (radial artery), time, and body position (prone) in all patients. The overall variability for the measurement of tHb in our Medical Center's central laboratory is consistently small (coefficient of variation: 0.8%-1.0%).…”
Section: Discussionmentioning
confidence: 99%
“…The overall variability for the measurement of tHb in our Medical Center's central laboratory is consistently small (coefficient of variation: 0.8%-1.0%). 13 Hospitals are required to intermittently confirm the variability of their measurement techniques.…”
Section: Discussionmentioning
confidence: 99%
“…First, tHb was measured using an automated gas analyser in the haematology laboratory to provide the reference haemoglobin values. Gehring et al [9] have reported significant intra-device and inter-device variation; therefore, it is important to remember that the reference device also has inherent errors. Second, although an important feature of SpHb is that it is non-invasive, our in-vivo adjustment method requires an invasive blood sample.…”
mentioning
confidence: 99%